Analysis of Crosstalk in the Mechanomyographic Signals Generated by Forearm Muscles During Different Wrist Postures - Islam, Anamul; Sundaraj, Kenneth; R. Badlishah, Ahmad; Ahamed, Nizam Uddin; Md. Asraf, Ali (Wiley, 2015)
In this study, we analyzed the crosstalk in mechanomyographic (MMG) signals generated by the extensor digitorum (ED), extensor carpi ulnaris (ECU), and flexor carpi ulnaris (FCU) muscles of the forearm during wrist flexion (WF) and extension (WE) and radial (RD) and ulnar (UD) deviations